PEMOLISIAN KOMUNITAS DAN DINAMIKA SOSIAL: MENGUNGKAP FAKTOR SOSIAL DALAM PENCEGAHAN DAN PENANGANAN ANAK KORBAN KEKERASAN ORANG TUA DI TANGERANG - Nadia Utami Larasati; Tiya Putri Maryani (Jurnal Analisa Sosiologi, 2024)
This article discusses the factors that cause parental violence against children as well as community-based prevention efforts to protect children. This research uses a descriptive qualitative approach. Research data was obtained by conducting interviews with 6 (six) research informants consisting of parents of perpetrators of violence, representatives of the Banten Province Child Protection Agency (LPA), psychologists, the community, and local community leaders. The Sociological Model of Child Abuse is used to analyze the causes of children becoming victims of parental violence. The community policing theory which includes 4 (four) variations, namely community policing, environmental security systems, surveillance, and citizen patrols is used to look at measures to prevent violence against children. The results of the research show that the determinants of children becoming victims of parental violence include the socio-economic status of the family, problems in marriage and household disorganization, as well as family size and the age range between children. In terms of community-based violence prevention, community efforts to protect children victims of parental violence in Tangerang have been carried out but strengthening efforts still need to be made to make them more effective. Therefore, this research also provides recommendations for action as a further prevention effort and treatment that also needs to be carried out for parents.